2022
DOI: 10.1177/09514848221109833
|View full text |Cite
|
Sign up to set email alerts
|

Causing harm but doing good: Recognizing and overcoming the burden of necessary evil enactment in healthcare service professions

Abstract: Necessary evils – defined as acts that cause physical, psychological, or emotional harm to victims but are for the greater good of either the victim or society - are an everyday occurrence in the healthcare industry across the globe and across healthcare service professions. Healthcare professionals are tasked with behaviors that result in pain and suffering (e.g. nurses providing shots to patients; oncologists communicating cancer diagnoses) for the betterment of their patients and stakeholders. Although thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In terminology, all such tasks have 'conflicted' or simultaneously antisocial (i.e., harmful) and prosocial (i.e., beneficial) impacts. Regardless of the potential for benefit to arise from the harm, performing these tasks is complex and imposes substantially different demands on workers than ones that are neutral or exclusively prosocial (Andiappan, 2023;Whiteside and Barclay, 2018). Thornton-Lugo and Rupp (2021) found that the negative emotional and cognitive implications of performing harmful tasks are not mitigated simply because they are required or done in the service of organizational goals.…”
Section: Harm-doing and Meaningfulness Of Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In terminology, all such tasks have 'conflicted' or simultaneously antisocial (i.e., harmful) and prosocial (i.e., beneficial) impacts. Regardless of the potential for benefit to arise from the harm, performing these tasks is complex and imposes substantially different demands on workers than ones that are neutral or exclusively prosocial (Andiappan, 2023;Whiteside and Barclay, 2018). Thornton-Lugo and Rupp (2021) found that the negative emotional and cognitive implications of performing harmful tasks are not mitigated simply because they are required or done in the service of organizational goals.…”
Section: Harm-doing and Meaningfulness Of Workmentioning
confidence: 99%
“…Previous research on organizationally mandated harm-doing has focused on the negative experiences of targets and actions that can be taken to lessen these outcomes, such as performing the tasks in an interactionally just or interpersonally sensitive manner (Hillebrandt et al, 2022;Margolis and Molinsky, 2008;Thornton-Lugo and Rupp, 2021). Performers' experiences have been either overlooked or considered only insofar as they limit or support actions that benefit targets (Andiappan, 2023;. Even actions taken to repair harm, although beneficial for targets, may worsen the situation for performers.…”
Section: Harm-doing and Meaningfulness Of Workmentioning
confidence: 99%
See 2 more Smart Citations